Trends of Augmented Reality in Science Education Studies in Elementary Schools: A Bibliometric Analysis from 2013 – 2023 - Lestari, Arista; Rohmani, Rohmani (FKIP Universitas Lampung, 2024)
In the digital era, education has undergone a significant transformation thanks to advancements in information and communication technology. Augmented Reality is an educational medium that utilizes the development of digital technology in its progress. This study aims to analyse research trends regarding the use of Augmented Reality in science education at the elementary school level. The method used is bibliometric analysis with documents sourced from the Scopus database within the last 10 years of publication (2013-2023). This analysis includes emerging themes related to Augmented Reality in science education at the elementary school level, as well as publication trends based on keywords. The results show that (a) there are four themes, namely the development of Augmented Reality media, the effectiveness of Augmented Reality in science education at the elementary school level, the implementation of Augmented Reality media in teaching, and the enhancement of critical and creative thinking skills; (b) one meta-theme, which is the use of Augmented Reality media to improve the quality of science education at the elementary school level; and (c) the keyword Augmented Reality is not yet connected to the keywords cooperative and collaborative learning, which represents a research gap that can be further explored in future studies. Keywords: augmented reality, science, elementary school, bibliometric analysis.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp814-826